The winter sea - Kearsley, Susanna, 1966- (Naperville, Ill. : Sourcebooks Landmark, 2010)
Author Carrie McClelland settles into Slains Castle to begin research for her next book, an epic tale about the 1708 attempt to return the exiled James Stewart to the throne, but when the lines between past and present begin to blur, Carrie is in danger of losing her grip on reality and must rely on the only person who might know the truth about long-past events.
Adult.
Adult
Keywords: Americans -- Scotland -- Fiction; Women authors -- Fiction; Americans -- Scotland -- Fiction; Love stories; Women authors -- Fiction; Scotland -- Fiction; Scotland -- Fiction; Love stories